PENGARUH KUALITAS PELAYANAN, CITRA MEREK DAN HARGA TIKET TERHADAP KEPUTUSAN PENGGUNAAN JASA PO RAMAYANA MAGELANG - Gesti Nopelia Anjarsari; Handoyo Djoko Waluyo (Jurnal Ilmu Administrasi Bisnis, 2017)
The increased needs of the community road transport services will trigger the growth of transportation business in the form of Company Otobus. The increasing mobility forcing consumers choosing alternative Otobus from various companies. Every companies must win the competition to attract consumer to use its services. This research focus to result that show usage of the decision in PO Ramayana Magelang obtained from responden.The purpose of this research is to know the influence of service quality, brand image and price of tickets against the decision of the use of PO Ramayana. This research type is explanatory research. Sampling techniques using non-probability sampling with accidental sampling and purposive sampling. As for the total sampleas many as 100 respondents. This program assisted by SPSS 21.0.Based on the descriptive analysis, indicating the variable quality of service are on a good categorization of 54%. Brand iage variable are at good categorization by 48%. Varible price of tickets are at very good categorization of 66% and use of decision are at high categorization of 71%. Multiple corelation coeficient based on obtained values of the corelation that indicates 0,620 is strong correlation. Based on determination of coefficient indicates that the variable service quality, brand image and price of tickets contributed amounted to 38,4% against of the use decision variable.